Comprehensive and Quality Analysis of Freeze-Dried Methylene Diphosphonate Labelled with Technetium-99m: An Extensive Comparison of Biodistribution Study with Commercial Standards (Bangladesh Journal of Nuclear Medicine, 2025)
Technetium-99m (99mTc) is an important radionuclide used for the prognosis of bone scintigraphy labeled with a suitable kit. The present investigations focus on the aseptic preparation and application of the methylene diphosphoni acid (MDP) kit on bio-organ after labeling with 99mTc collected from a 99Mo/99mTc generator. Before going to the bio-application of the labeled kit, radiochemical purity was determined by paper chromatography using the high-purity germanium (HPGe) detector, and the radiochemical purity of 99mTc-MDP was found to be 99%. Furthermore, negative results were found for pyrogen and bacterial endotoxin tests; fungal growth was also absent. Radiation dose uptake in different organs of Wistar rats was measured by a dose calibrator, and observed results indicate the highest accumulation of 99mTc-MDP in the skull and skeletal part. This study also performed a comparative study model between laboratory and commercially prepared Monrol MDP kits. This study was performed as a bio-application of laboratory-prepared 99mTc-MDP prior to commercial production of cold kits at the radioisotope production division of the Bangladesh Atomic Energy Commission (BAEC). Overall, the observations from this study are within the accepted range and provide prospects for commercial production of the kits for human administration.Bangladesh J. Nuclear Med. 27(2): 245-252, 2024